Manipulasi Pencatatan Nikah pada Aplikasi Sistem Informasi Manajemen Nikah (SIMKAH) di KUA Kecamatan Sangatta Selatan Perspektif Hukum Positif dan Maq??id Asy-Syar??ah - Ghozali, Imam; Alfitri, Alfitri; Haries, Akhmad (Bulletin of Community Engagement, 2024)
The background of this research is to observe the reality that occurs in the field related to marriage registration, which seems to involve 'manipulation' of the date of the marriage contract that does not correspond to the existing reality. This clash arises because the latest PMA Number 20 of 2019 states that the registration of the intention to marry must be done at least 10 (ten) working days before. However, the public still follows the old culture, where marriage registration can be done a week or even a few days before the marriage contract is set. This research aims to identify the causes of 'manipulation' of marriage registration in the marriage management information system application (SIMKAH), examine the perspective of positive law regarding the 'manipulation' of marriage registration, and understand the view of maq??id al-shar??ah regarding this practice. This research is a type of normative empirical. The results of this study indicate the occurrence of data manipulation in marriage registration within less than 10 (ten) days due to several factors. First, there is a lack of knowledge among prospective brides and grooms. Second, there are events beyond control, such as pregnancies outside of marriage. Third, local customs and traditions dictate choosing auspicious or aesthetically pleasing dates for weddings. The implementation of the SIMKAH Online system at the Religious Affairs Office (KUA) in South Sangatta District has been effective in recording marriages. This is in accordance with Minister of Religious Affairs Regulation Number 19 of 2018 concerning marriage registration. From the perspective of Islamic Law, the implementation of SIMKAH Online at the KUA of South Sangatta District has fulfilled the requirements stipulated in the theory of mashlahah mursalah related to the determination of marriage registration laws that align with the objectives of maq??id asy-syar??ah. Keywords: Manipulation of Marriage Registrational, Sistem Informasi Manajemen Nikah